The role of Nb2O5deposition process on perovskite solar cells - Fernandes, Silvia L. [UNESP]; Garcia, Larissa De O. [UNESP]; Júnior, Roberto De A. Ramos [UNESP]; Affonço, Lucas J. [UNESP]; Bagnis, Diego; Vilaça, Rodrigo; Pontes, Fenelon M. [UNESP]; Da Silva, José H. D. [UNESP]; Graeff, Carlos F. O. [UNESP] (AIP Publishing, 2022)
Two different methods are used to deposit Nb2O5 as compact electron transport layers in n-i-p double cation mixed-halide perovskite Cs0.17FA0.83Pb(I0.83Br0.17)3 solar cells: reactive sputtering and spin coating. These different Nb2O5 films influenced perovskite growth and the charge transport in the cells. Photovoltaic parameters were obtained with an average power conversion efficiency of 17.0% and 15.7% for the devices based on sputtered and spin-coated Nb2O5, respectively. The mobility and the extracted charges were higher in sputtered Nb2O5-based devices than in the spin-coated ones. This effect is attributed to the larger grain sizes observed in the perovskite films when deposited onto the sputtered Nb2O5 layers. The higher densities of grain boundaries in the spin-coated Nb2O5-based devices increase ion diffusion and are expected to decrease efficiency.